Product Selectivity Control under Acidic and Basic Conditions on Oxidative Transformation of 1,3-Dicarbonyls Using Sodium Hypochlorite Pentahydrate - Kirihara, Masayuki; Sakamoto, Yugo; Tanaka, Takumi; Kawai, Takuma; Okada, Tomohide; Kimura, Yoshikazu; Takizawa, Shinobu (Synthesis, 2024)
In this study, we reported that the reactivity of 1,3-dicarbonyls with sodium hypochlorite pentahydrate (NaOCl·5H2O) as an easy-to-handle oxidant, alters greatly depending on the pH value. The reaction of NaOCl·5H2O under weakly basic conditions (pH 12) gives the corresponding carboxylic acids in up to 97% yield. Upon addition of AcOH (pH 5), chlorination of active methylene sites proceeds efficiently to afford dichlorinated products in high yields.
Keywords: 1,3-dicarbonyls; sodium hypochlorite pentahydrate; cleavage; dichlorination; selective oxidation